Dari Ushul Fiqh Menuju Filsafat Fiqh: Membaca Gagasan ‘Abd al-Jabbar ar-Rifa’i Tentang Filsafat Fiqh - Dimyati, Ahmad (The Institute of Research and Service Community IPMAFA Pati, 2024)
This article intends to elaborate in depth on Abd al-Jabbar ar-Rifa'i's (AJR) thoughts about the philosophy of fiqh. This topic is particular because AJR explicitly uses the term the philosophy of fiqh as a new study in Islamic law, as a new branch of ushul fiqh. To deeply explain the concept of the philosophy of fiqh and its position in Islamic law studies, the author uses qualitative descriptive research with a philosophical approach, especially the philosophy of science. This research found that AJR limits the philosophy of fiqh in a loose definition, whereas a material object, fiqh, is approached with a philosophical and sociological perspective. The philosophy of fiqh is also compared with other traditions in Islamic law studies, such as ushul fiqh and maqashid asy-syari’ah. With these broad boundaries, the AJR concept of the philosophy of fiqh is flexible. It opens up opportunities for developing broad fiqh studies when faced with developments in modern science and responding to various contemporary problems the Muslim community faces. The philosophy of fiqh in this article also shows the shifting paradigm cycle in the study of fiqh or Islamic law.